Respuesta :

Answer:

Simplifying

5n + -9 + 6 = -20

Reorder the terms:

-9 + 6 + 5n = -20

Combine like terms: -9 + 6 = -3

-3 + 5n = -20

Solving

-3 + 5n = -20

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '3' to each side of the equation.

-3 + 3 + 5n = -20 + 3

Combine like terms: -3 + 3 = 0

0 + 5n = -20 + 3

5n = -20 + 3

Combine like terms: -20 + 3 = -17

5n = -17

Divide each side by '5'.

n = -3.4

Simplifying

n = -3.4

Step-by-step explanation: